Herbivoria em Bauhinia rufa (Leguminosae: Caesalpinioideae) em fragmentos de cerrado - Quinalha, Marília Monteiro [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Herbivory is the basal link among the trophic chains and therefore has great importance in the energy flow in the ecosystems. However, the ecological interactions have been changed due to the process of fragmentation that has occurred in the cerrado. Thus, our objective was to evaluate the herbivory and the presence of possible constituents of defense in leaves of Bauhinia rufa in two cerrado fragments of different sizes . We evaluated in both of them species richness and abundance of herbivores as well absolute herbivory ( n = 25 plants / fragment ) . Through histochemical tests and scanning electron microscopy we verified the constituents of defense. The difference between the herbivory in the fragments was not statistically significant ( t = -1.387 , p = 0.166 ) . However , we found a higher abundance of morphotypes of herbivores in the smaller fragment. We detected chemical and physical constituents that may confer protection to the plant at all stages of leaf development. Although several publications have indicated that small fragments have a higher susceptibility to changes, our study revealed no effect of fragment size on the absolute herbivory, suggesting that there are other factors acting more strongly and maintaining this type of interaction in these ecosystems

A herbivoria representa o elo basal entre as cadeias tróficas e, portanto, exerce grande importância no fluxo de energia nos ecossistemas. Porém, com o processo de fragmentação que vem ocorrendo no cerrado, interações ecológicas estão sendo alteradas. Assim, nosso objetivo foi avaliar a herbivoria e a presença de possíveis constituintes de defesa em folhas de Bauhinia rufa em dois fragmentos de cerrado de distintos tamanhos. Em ambos avaliamos a riqueza e abundância de herbívoros, bem como a herbivoria absoluta (n=25 plantas/fragmento). Através de testes histoquímicos e microscopia eletrônica de varredura verificamos os constituintes de defesas. A herbivoria não diferiu estatisticamente entre os fragmentos (t= -1,387, p= 0,166). Entretanto, encontramos maior abundância de morfotipos de herbívoros no fragmento menor. Detectamos constituintes químicos e físicos, que podem conferir proteção à planta, em todos os estádios de desenvolvimento da folha. Embora diversas publicações indiquem que fragmentos pequenos apresentam maior susceptibilidade a alterações, nosso estudo não revelou efeito do tamanho do fragmento sobre a herbivoria absoluta e componentes de defesa das plantas, sugerindo que há outros fatores que atuam mais fortemente mantendo esse tipo de interação nesses ecossistemas
Herbivory of Bauhinia rufa ( Leguminosae : Caesalpinioideae ) in fragments of cerrado
Keywords: Herbivoria; Pata de vaca; Cesalpinacea; Herbivoro; Herbivory